IMPROVING THE SKILLS OF CHOOSING DRUGS USING THE CBIA METHOD IN THE COMMUNITY OF MAJELIS TAKLIM NURUZHOLAM CILEMPUYANG VILLAGE - Muhibatul Lailiah; Yuhansyah Nurfauzi; Mika Tri Kumala Swandari (International Journal of Islamic and Complementary Medicine, 2023)
Housewives are the "key person" in the use of drugs at home (Handayani, 2018). According to the results of a survey conducted by researchers in January 2022, the percentage of the Nuruzholam Taklim congregation who practice self-medication or self-medication is 69%. The use of over-the-counter and over-the-counter medicines was limited by 63%, which kept the medicine 57% and 58.7% disposed of the medicine incorrectly. The CBIA (Community Based Interactive Approach) program can be a solution to existing problems. CBIA is one of the community empowerment activities that can be used to educate the wider community about the selection and use of drugs that are suitable for self-medication or the use of over-the-counter drugs and limited over-the-counter drugs or those included in OTC (over-the-counter) (Bela & Suryawati, 2016). This study aims to determine the knowledge and skills of using drugs and to determine the effect of applying the CBIA method to increase knowledge about drugs in the Majelis Taklim Nuruzholam. This research method is quantitative research with Quasi-Experimental Design, one-group pretest-posttest. Sampling using purposive sampling method obtained 60 respondents who have met the inclusion and exclusion criteria. Analysis of the data used is statistical test paired t-test and get a significance value (2-tailed) of 0.000 <0.05, indicating a significant difference between the pretest-posttest values. The CBIA program is effective in increasing knowledge of the Majelis Taklim Nuruzholam Community in Cilempuyang Hamlet.